The practices of nasi ambeng among modern Javanese Community in Malaysia / Muhammad Shahrul Mohd Suleiman, Mohd Shazali Md Sharif and Zatul Iffah Mohd Fuza - Mohd Suleiman, Muhammad Shahrul; Md Sharif, Mohd Shazali; Mohd Fuza, Zatul Iffah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The intermingling of the Javanese and Malay cultures through assimilation, acculturation, and crosscultural marriages has given rise to the emergence of the Javanese-Malay population. Over time, this population has evolved into a distinct Malay sub-ethnic group in Malaysia, undergoing various adaptations and adoptions, including their culinary traditions. However, there is a limited empirical understanding of the extent to which Javanese traditional food, particularly Nasi Ambeng, is practiced within this community, thus this scholarly investigation strives to actively foster and enrich present-day knowledge and profound perspectives, with a specific focus on advancing the realm of Malay gastronomic studies. To address this gap, this study employs ethnographic and netnographic approaches to investigate the contemporary practices of serving Nasi Ambeng. In order to obtain an exhaustive and comprehensive dataset, purposive sampling was employed, specifically targeting the concentrated Javanese-Malay population residing in specific regions of Johor and Selangor. The findings shed light on the fact that the modern Javanese in Malaysia have expanded the scope of Nasi Ambeng beyond its traditional role in feasts and ceremonial activities. It is revealed that Nasi Ambeng is also commonly served for family consumption and during business-related engagements. Through this research, it becomes evident that the preservation and perpetuation of traditional foods like Nasi Ambeng rely heavily on the practices of the community, irrespective of any adaptations made to align with the evolving needs and progress of the wider society.